STUDY OF OPTOELECTRONIC PROPERTIES OF POLYANILINE/CARBON MATERIALS BLENDS AS COUNTER ELECTRODES IN DSSC (DYE- SENSITIZED SOLAR CELL) - Tanudjaja, Alvin
Polyaniline (PANI) is a conductive polymer which its conductivity depends on the level and type of doping. In this study, PANI synthesized in the form of emeraldine salt (ES) and varied composition in the form of a blend with graphite or carbon black, which is used as the counter electrode in DSSC (Dye-Sensitized Solar Cell) device. Composition of PANI/graphite blend or PANI/carbon black blend was varied by 5, i.e. pure PANI; pure graphite or carbon black; blend of PANI/graphite or PANI/carbon black with mass ratio of 3:1; 1:1; and 1:3. For both PANI/graphite blend and PANI/carbon black blend with a ratio of 1:3, annealing processes were carried out at various temperatures, starting from room temperature, 50, 80, 100, 120, 150, up to 180 oC. PANI/graphite samples and PANI/carbon black samples were characterized using FTIR spectroscopy, UV-Vis reflectance spectroscopy, Raman spectroscopy, and the conductivity measured using LCR meter, IR absoprtion, Raman, and UV-vis reflectance spectra of the PANI/graphite or PANI/carbon black blend with a mass ratio of 1: 3 shows the dominant feature of graphite or carbon black respecttively. DSSC characterization using a solar simulator shows that the counter electrodes made of PANI/graphite 1:3 (25% w/w PANI) produced the highest efficiency of 1.51%, where annealing of this cell at the 120 oC improve further the efficiency significantly up to 2.32%. In the case of PANI/carbon black blend counter electrode with mass ratio of PANI/carbon black 1:3 (25% w/w PANI), produced a cell with efficiency of 0.37%, annealing at 150 oC improved the cell efficiency more than 5- fold up to 2.01%.